Urticarial rash as the initial presentation of COVID‐19 infection: A case report - Usamah Al‐Anbagi (14778037) (2023)
During the COVID-19 pandemic, various skin manifestations have been described. These include an urticarial rash, morbilliform rash, maculopapular rash, vascular lesions, and varicella-like eruptions. A 30-year-old woman presented with a mild cough, then hives and pruritic rash for 3 days, followed by fever, dyspepsia, and throat pain for one day. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.6076